Hybrid Control for Bidirectional Z-Source Inverter for Locomotives. (15th February 2015) - Vijayan, Vasanthi; Ashok, S.
Abstract : Electric traction uses three phase locomotives in main line services. Three phase locomotives consist of voltage source inverters for driving the traction motors. This paper proposes a hybrid algorithm for bidirectional Z-source inverters in accelerating region of operation of locomotives. The speed control method adopted is same as that in the existing three phase locomotives which is variable voltage variable frequency. Bidirectional Z-source inverter is designed for getting the same output power as in voltage source inverter fed locomotives. Simulation is done in all regions of traction speed curve, namely, acceleration, free running, and braking by regeneration. The voltage stress across the devices and modulation index are considered while analyzing the proposed control algorithm. It is found that the modulation index remains at a high value over the entire range of frequencies. Due to the higher value of modulation index the harmonics in the inverter output voltage is reduced. Also the voltage stress across devices is limited to a value below the device rating used in the present three phase locomotives. A small scale prototype of the bi-directional Z-source inverter fed drive is developed in the laboratory and the hybrid control was verified in the control topology.